Determination of trace cobalt ions in bottled drinking water samples from Fiji Island by spray-assisted fine droplet formation-liquid phase microextraction based on simultaneous complexation and extraction before flame atomic absorption spectrometer measurement - Sagsoez, Oguzhan; Arvas, Buesra; Zaman, Buse Tugba; Yolacan, Cigdem; Bakirdere, Sezgin (SPRINGER, 2023)
the FAAS system was enhanced to about 110-folds with respect to 2.2 ng mL(-1) detection limit calculated for the proposed method. Bottled drinking water samples from Fiji Islands were used to demonstrate the applicability of the developed method for the accurate determination of trace cobalt in real sample matrices. Percent recovery results obtained between 95.5 and 88.5% showed the suitability of the developed method in the determination of cobalt at trace levels even in complex sample matrices. In this study, a green, simple and effective preconcentration method named as spray-assisted fine droplet formation-liquid phase microextraction (SAFDF-LPME) before the flame atomic absorption spectrophotometry (FAAS) measurement for cobalt determination was developed. The method reduces the external dispersive solvent usage by using a simple spraying apparatus to obtain fine droplets of the extraction solvent. SAFDF-LPME method also consists of simultaneous complexation and extraction which indicates the environmental benevolence of the developed method. This method minimized the relative errors with high repeatability and accuracy by reducing the experimental steps. The influential parameters such as buffer type, buffer solution volume, extraction solvent/ligand solution volume (spraying cycle), and mixing period were systematically optimized by the univariate optimization procedure. With the optimum parameters applied, the detection power of
Keywords: Cobalt; Simultaneous complexation and extraction; Slotted quartz tube; FAAS; Fiji water; GAS-CHROMATOGRAPHY; ICP-OES; PRECONCENTRATION; NICKEL; Environmental Sciences & Ecology